Bio-functionalized magnetic nanoparticles for the immunoassay of fetal fibronectin: a feasibility study for the prediction of preterm birth - Wong, Chian-Huey (Sci Rep, 2017)
Preterm birth is an important cause of perinatal morbidity and mortality. Various biomarkers in cervicovaginal secretions related to preterm birth have been investigated, of which foetal fibronectin (fFN) shows the greatest potential because of its high negative predictive value. The immunomagnetic reduction (IMR) assay has emerged as a novel quantitative method to detect biomarkers. In this prospective case-control study, we analysed 33 samples of cervicovaginal secretions from pregnant women between 22 and 34 weeks of gestation at high risk of preterm birth. Seventeen samples were from women with term deliveries and 16 from those with preterm deliveries. The fFN concentration in each sample was measured using both an IMR assay and enzyme-linked immunosorbent assay (ELISA). The low detection limits of the IMR assay and ELISA were 0.0001 ng/mL and 0.789 ng/mL, respectively. The sensitivity and specificity of the IMR assay were 0.833 and 0.944, respectively, compared to 0.583 and 0.611 by ELISA. Our results suggest that measuring the concentration of fFN with the IMR assay is a good alternative method to accurately predict the risk of preterm birth.